Antitrust Practices Challenges in The Digital Economy, Review - Ludmila MOGILDEA; Ina MOGILDEA; Constanta Laura AUGUSTIN (ZUGRAVU); Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2021)
The aim of the paper is to review antitrust practices in the digital age, where competition is taking on new forms and content in new markets where they tend to have an absolute monopoly. Thus, more and more often we witness the fact that products on digital markets are evolving so fast that the bodies that fight against the monopoly fail to analyze these new markets, less to react.
Keywords: Antitrust Practices; Digital Economy.